STAGES OF DEVELOPMENT OF TEACHER PROFESSIONAL COMPETENCE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article discusses the stages of development of a teacher’s professional competence throughout his entire professional activity: initial, basic and post-basic. These stages are compared with levels of mastery of professional knowledge and skills, with the acquisition of experience, the development of pedagogical skills. Author analyzes the stages of professional and life crises in order to successfully overcome them on the path to true professionalism.